The butterfly effect [videorecording (DVD)] - Gruber, J. Mackye; Bress, Eric; Kutcher, Ashton, 1978-; Walters, Melora; Smart, Amy, 1976- (Infinifilm., 2004)
Evan Treborn wants to be free of his disturbing childhood memories. As a young child, he often blacked out for long periods of time and would try to detail his life through journal writing. As a young adult, he revisits the journal entries to figure out the truth about his troubled childhood friends Kayleigh, Lenny, and Tommy. When he discovers he can travel back in time in order to set things right, he does so in order to save his beloved friends. But he discovers that for every change he makes in the past, there is an unexpected consequences in the future.